Reflections From a Post-Pandemic Library (Journal of EAHIL, 2022)
One of the many lessons learned from the Covid-19 pandemic is the importance of connecting and collaborating with students and staff in and outside the library. Because of Covid, the interaction was kept at a minimum and limited to the occasional zoom-based lectures or individual instructions. After reopening our library, we experienced a dramatic drop in library visits and library use. In this reflective text, we discuss the challenges we faced as we returned to a new normal.